Feigenbaum's echocardiography - Armstrong, William F.; Ryan, Thomas 1953-; Feigenbaum, Harvey (Wolters Kluwer, 2019)
"Publisher's Note: Products purchased from 3rd Party sellers are not guaranteed by the Publisher for quality, authenticity, or access to any online entitlements included with the product. Continuing the long-standing Feigenbaum tradition as an authoritative, comprehensive echocardiography resource, the thoroughly revised Feigenbaum's Echocardiography, Eighth Edition, helps echocardiographers, fellows, clinicians, and sonographers master the art and science of echocardiography and stay current with all that's new in the field. Written by William F. Armstrong and Thomas Ryan, it guides you through pertinent physics, technology, clinical applications, and new developments in the field.
Keywords: Ultraschallkardiografie; Echocardiography / methods; Heart Diseases / diagnosis; Echocardiography